Conventional Hospitalization versus Sequential Outpatient Parenteral Antibiotic Therapy for Staphylococcus aureus Bacteremia: Post-Hoc Analysis of a Multicenter Observational Cohort - Nerea Castillo-Fernández; Pedro María Martínez Pérez-Crespo; Elena Salamanca-Rivera; Laura Herrera-Hidalgo; Arístides de Alarcón; María Dolores Navarro-Amuedo; Teresa Marrodán Ciordia; María Teresa Pérez-Rodríguez; Juan Sevilla-Blanco; Alfredo Jover-Saenz; Jonathan Fernández-Suárez; Carlos Armiñanzas-Castillo; et al. (MDPI AG, 2023)
It is not known whether sequential outpatient parenteral antimicrobial (OPAT) is as safe and effective as conventional hospitalization in patients with S. aureus bacteremia (SAB). A post-hoc analysis of the comparative effectiveness of conventional hospitalization versus sequential OPAT was performed in two prospective Spanish cohorts of patients with S. aureus bacteremia. The PROBAC cohort is a national, multicenter, prospective observational cohort of patients diagnosed in 22 Spanish hospitals between October 2016 and March 2017. The DOMUS OPAT cohort is a prospective observational cohort including patients from two university hospitals in Seville, Spain from 2012 to 2021. Multivariate regression was performed, including a propensity score (PS) for receiving OPAT, stratified analysis according to PS quartiles, and matched pair analyses based on PS. Four hundred and thirteen patients were included in the analysis: 150 in sequential OPAT and 263 in the full hospitalization therapy group. In multivariate analysis, including PS and center effect as covariates, 60-day treatment failure was lower in the OPAT group than in the full hospitalization group (p < 0.001; OR 0.275, 95%CI 0.129-0.584). In the PS-based matched analyses, sequential treatment under OPAT was not associated with higher 60-day treatment failure (p = 0.253; adjusted OR 0.660; % CI 0.324-1.345). OPAT is a safe and effective alternative to conventional in-patient therapy for completion of treatment in well-selected patients with SAB, mainly those associated with a low-risk source and without end-stage kidney disease.